Revitalisasi Pendidikan Karakter Berbasis Pancasila Dalam Pembinaan Remaja Putus Sekolah - Meli, Meli; Nurdin, Erni; Yudianto, Ahmad (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the revitalization of Pancasila-based character education in the development of dropout adolescents at the Palu Children's Social Institution UPT. Dropout adolescents face the risk of identity crisis, behavioral deviation, and weak value orientation. Character education is an important strategy to form an independent and moral person. The approach of this research is qualitative descriptive with a case study strategy. Data collection techniques include in-depth interviews, participatory observation, and documentation. The results of the study indicate that character education is implemented through habituation and role models, with the integration of Pancasila values ​​in development activities, such as worship, group discussions, social cooperation, and division of tasks. Supporting factors include the commitment of the mentor, cross-institutional cooperation, and the religious environment of the institution. The obstacles include the social background of adolescents, limited facilities, and lack of mentor training. Pancasila-based character education that is implemented contextually and consistently can strengthen the moral and social identity of dropout adolescents.